Optimization of Sodium Dodecyl Sulphate Loading in Poly (Vinyl Alcohol)-Water Coatings - Sharma, Ishita (My University, 2018)
The residual solvent study in poly (vinyl) alcohol-water based system has been investigated. The effect of anionic surfactant: sodium dodecyl sulphate (SDS), on the drying behavior of coatings has been investigated. Attempts were made to optimize the surfactant loading in order to minimize the residual solvent and drying time. Surfactant loadings were changed from 0.5% to 2.5% by weight. Residual solvent left was 5.88% in poly (vinyl) alcohol-Water, 4.88% in Poly (vinyl) alcohol-sodium dodecyl sulphate (0.5%)-Water, 4.17% in poly(vinyl) alcohol- sodium dodecyl sulphate (1%)-Water 3.85% in poly(vinyl) alcohol- sodium dodecyl sulphate (1.5%)-Water, 3.27% in poly(vinyl) alcohol- sodium dodecyl sulphate (2%)-Water and 2.54% in poly(vinyl) alcohol- sodium dodecyl sulphate (2.5%)-Water for 0.5 wt.%. Effect of initial coating thickness on residual solvent were also investigated. Optimum surfactant loading becomes out to be independent of initial coating thickness.
Master of Science- Chemistry
Keywords: Residual solvent; Polymeric coatings; Surfactant enhanced drying; Sodium dodecyl sulphate; Drying time; Optimization